Efficacy, Safety and Tolerability of Pyronaridine-artesunate in Asymptomatic Malaria-infected Individuals: a Randomized Controlled Trial. (13th May 2021) - Dabira, Edgard D; Hachizovu, Sebastian; Conteh, Bakary; Mendy, Alieu; Nyang, Haddy; Lawal, Bolarinde; Ndiath, Mamadou Ousmane; Mulenga, Joyce M; Mwanza, Sydney; Borghini-Fuhrer, Isabelle; Arbe-Barnes, Sarah; Miller, Robert; et al.
Abstract: Background: Pyronaridine-artesunate (PA) is a registered artemisinin-based combination therapy, potentially useful for mass drug administration campaigns. However, further data are needed to evaluate its efficacy, safety and tolerability as full or incomplete treatment in asymptomatic Plasmodium falciparum -infected individuals. Methods: This phase II, multi-center, open label, randomized clinical trial was conducted in The Gambia and Zambia. Participants with microscopically confirmed asymptomatic P. falciparum infection were randomly assigned (1:1:1) to receive a 3-day, 2-day, or 1-day treatment regimen of PA (180:60 mg), dosed according to bodyweight. The primary efficacy outcome was polymerase chain reaction (PCR)-adjusted adequate parasitological response (APR) at day 28 in the per-protocol population. Results: A total of 303 participants were randomized. Day 28 PCR-adjusted APR was 100% for both the 3-day (98/98) and 2-day regimens (96/96), and 96.8% (89/94) for the 1-day regimen. Efficacy was maintained at 100% until day 63 for the 3-day and 2-day regimens but declined to 94.4% (84/89) with the 1-day regimen. Adverse event frequency was similar between the 3-day (51.5% [52/101]), 2-day (52.5% [52/99]), and 1-day (54.4% [56/103]) regimens; the majority of adverse events were of grade 1 or 2 severity (85% [136/160]). Asymptomatic, transient increases (>3 times the upper limit of normal) in alanine aminotransferase/aspartate aminotransferase were observed for 6/301 (2.0%) participants. Conclusions: PA had high efficacy and good tolerability in asymptomatic P. falciparum- infected individuals, with similar efficacy for the full 3-day and incomplete 2-day regimens. Although good adherence to the 3-day regimen should be encouraged, these results support the further investigation of PA for mass drug administration campaigns. Clinical Trials Registration: NCT03814616. Abstract : This randomized study in The Gambia and Zambia evaluated pyronaridine-artesunate as full or incomplete treatment in individuals with asymptomatic Plasmodium falciparum infection. High efficacy and good tolerability suggest that pyronaridine-artesunate could be useful in mass drug administration campaigns in Africa.